Frontispiece: Uncovering Key Structural Features of an Enantioselective Peptide‐Catalyzed Acylation Utilizing Advanced NMR Techniques. Issue 51 (12th December 2016) - Procházková, Eliška; Kolmer, Andreas; Ilgen, Julian; Schwab, Mira; Kaltschnee, Lukas; Fredersdorf, Maic; Schmidts, Volker; Wende, Raffael C.; Schreiner, Peter R.; Thiele, Christina M.
Abstract : NMR Spectroscopy In their Communication onpage 15754 ff., P. R. Schreiner, C. M. Thiele et al. apply newly developed NMR experiments to confirm the mechanism of a highly enantioselective acylation reaction. Dispersion interactions between catalyst and substrate are key to the reaction.